The Relationship Between Body Image and Self-Confidence Among Gym Members - Taniady, Vania; Murti, Heru Astikasari Setya (Kuras Institute, 2024)
As a teenager, you often face many changes, especially internal body image and self-confidence. This research aims to understand the relationship between body image and self-confidence in gym members. The research method used is quantitative with a correlational design to statistically measure and statistically analyze the relationship between body image and self-confidence. A total of 117 gym members in Salatiga were research subjects. They were selected using an accidental sampling technique, which means they were chosen by chance from the available population. The data analysis method used for the correlation test uses Spearman’s Rho. The research results show a positive relationship between body image and self-confidence. That is when someone has a positive perception of body image and tends to have self-confidence. The Spearman's Rho correlation coefficient value of .617 indicates that this relationship is strong. In addition, a significance value (sig.) of .000 indicates that this relationship does not occur by chance. The results of this study suggest that increasing body image can help improve self-confidence. Thus, this research provides positive insight into the relationship between body image and self-confidence in gym members, which can help them improve their self-perception and self-confidence.